Motivated social categorization fundamental motives enhance people's sensitivity to basic social categories. [article]. - Maner, Jon K.
This article presents an evolutionary framework for identifying the characteristics people use to categorize members of their social world. Findings suggest that fundamental social motives lead people to implicitly categorize social targets based on whether those targets display goal-relevant phenotypic traits. A mate-search prime caused participants to categorize opposite-sex targets (but not same-sex targets) based on their level of physical attractiveness (Experiment 2). A self-protection prime interacted with chronic beliefs about danger, increasing participants' tendency to categorize targets based on their racial group membership (Back or White; Experiment 3). This work demonstrates that people categorize others based on whether they display goal-relevant characteristics reflecting high levels of perceived desirability or threat. Social categorization is guided by fundamental evolved motives designed to enhance adaptive social outcomes. - (from the authors)
Keywords: Miller, Saul L; Motivation; Categorization; Evolutionary psychology; Mating; Prejudice